Akibat Hukum Perceraian terhadap Harta Bersama pada Pasangan Tanpa Perjanjian Perkawinan dan Istri yang Menjalankan Kewajiban Suami dalam Mencari Nafkah Berdasarkan Perspektif Hukum Perkawinan dan Kompilasi Hukum Islam - Nadhira Zahra Farida; Djanuardi Djanuardi; Sherly MIS (Pusat Riset dan Inovasi Nasional, 2024)
In the context of marriage law in Indonesia, divorce brings a number of legal consequences, one of which is the division of joint property. This situation becomes more complex when the couple does not have a marriage agreement and when the wife carries out her husband's obligations in earning a living. Examples of cases like this are contained in Supreme Court Decision Number 266/K/AG/2010 and Supreme Court Decision Number 1636/K/Pdt/2018. This research aims to explain the legal provisions and legal consequences of divorce on the distribution of joint assets between couples without a marriage agreement and wives who carry out their husband's obligations based on the perspective of marriage law and Islamic law. This research uses a normative juridical approach with analytical descriptive research specifications. Data collection techniques were carried out through literature study and interviews. The data analysis method used is qualitative juridical. The research results show that in resolving the implementation of the division of joint assets in marriage in Indonesia, legal practitioners can be guided by the Marriage Law and the Civil Code as the legal basis for resolving the division of marital assets. This is in accordance with Article 37 of the Marriage Law which states that in the event of a divorce, joint property is regulated according to respective laws. However, if there is a case where the wife carries out her husband's obligations in terms of earning a living, it will be returned in accordance with the Judge's decision based on consideration of supporting evidence and the portion of each party's contribution to the joint assets collected.